Occurrence Download - Occdownload Gbif.Org (The Global Biodiversity Information Facility, 2020)
A dataset containing 2923652 species occurrences available in GBIF matching the query: { "and" : [ "Country is Japan", "TaxonKey is Plantae" ] } The dataset includes 2923652 records from 435 constituent datasets: 256 records from Marie-Victorin Herbarium (MT) - Plantes vasculaires. 1343 records from Bryophyte specimens of Iwate Prefectural Museum. 4402 records from Bryophyte specimens of Toyama Science Museum. 1 records from KUBI Paleobotany Collection. 57 records from University of Florida Herbarium (FLAS). 41992 records from Vascular Plants Collection of Sagamihara City Museum. 1 records from TEPB - Herbário Graziela Barroso. 93 records from Canadian Museum of Nature Herbarium. 7 records from Banco de Germoplasma del Real Jardín Botánico Juan Carlos I. 297 records from E. C. Smith Herbarium (ACAD) - Nova Scotia Museum of Natural History. 2 records from (Table T2) Calcareous nannofossil stratigraphy in ODP Hole 186-1151C sediments. 3677 records from Royal Botanic Garden Edinburgh Living Plant Collections (E). 887 records from Meise Botanic Garden Herbarium (BR). 30 records from R. L. McGregor Herbarium Vascular Plants Collection. 1341 records from Plant specimens of Takatsuki Nature Museum (Aquapia Akutagawa). 62324 records from Herbarium Specimens of Museum of Nature and Human Activities, Hyogo Pref., Japan. 59 records from Marie-Victorin Herbarium (MT) - Bryophytes. 1 records from SMNS Palaeontological collection - Fossil plants. 314 records from University of Vienna, Institute for Botany - Herbarium WU. 48669 records from Macroalgal collection of National Museum of Nature and Science (TNS). 10627 records from Bryophyte specimens of The Nagoya University Museum. 9 records from University of Guam Insect Collection. 500 records from Plant specimens of Oiso Municipal Museum. 58 records from Buffalo Society of Natural Sciences Clinton Herbarium. 3 records from Museu de Ciències Naturals de Barcelona: BGJBB. 111 records from Canadian Museum of Nature Palynology Collection. 249 records from MEXU/Colección de Briofitas. 456 records from CZE National PGR Inventory. 17 records from Bryophyte herbarium, Tromsø Museum. 15649 records from Plant specimens of Komatsu City Museum. 62 records from Herbarium Hamburgense. 1 records from Bell Museum algae. 6077 records from Vascular plant specimens of Iida City Museum. 1 records from PlutoF platform observations. 10 records from The Vascular Plants Collection of the University of Goettingen. 21 records from Instituto de Botánica Darwinion. 6 records from Microbial community structure or iron oxyhydroxides rich mound in Satsuma Iwo-jima, Japan. 3 records from Herbario de Plantas Vasculares de la Universidad de Salamanca: SALA. 1 records from Colección científica del Museo de Historia Natural Alfredo Dugés. 2006 records from Moscow University Herbarium (MW). 6107 records from Vascular Plants Specimens of Ehime Prefectural Science Museum. 12256 records from Geographically tagged INSDC sequences. 71 records from University of South Florida Herbarium (USF). 2406 records from Bernice P. Bishop Museum. 7 records from Banco de datos florísticos del Herbario CHAP. 1 records from CESJ - Herbário Leopoldo Krieger. 11 records from The Erysiphales Collection at the Botanische Staatssammlung München. 13 records from The digitization of plant specimens of NTU. 32 records from Central Siberian Botanical Garden Herbarium (NS, NSK). 324 records from A crowdsourcing approach to collecting photo-based insect and plant observation records. 109434 records from Plant Specimens of Kurashiki Museum of Natural History. 311 records from Museo Argentino de Ciencias Naturales "Bernardino Rivadavia" (MACN). Cryptogamic National Collection (BAc). 153 records from DAO Herbarium Type Specimens. 1401 records from University of North Carolina at Chapel Hill Herbarium. 348 records from Neptune Deep-Sea Microfossil Occurrence Database. 1587 records from Algae collection of Museum of Natural and Environmental History, Shizuoka. 4909 records from Plant specimens of Otaru City Museum. 805 records from Exploring Fronts With Multiple Robots – Schmidt Ocean Institute Cruise to the Pacific Ocean in 2018. 102 records from Field Museum of Natural History (Geology) Paleobotany Collection. 11 records from Wilson Botanical Garden - Las Cruces Biological Station. 410 records from Centre for Genetic Resources, the Netherlands, PGR passport data. 151592 records from The 2-5th National Survey on the Natural Environment: Vegetation Survey. 1 records from Vivero de Frutilla del Banco de Germoplasma de Frutilla - Universidad Nacional de Tucumán, Argentina. 47 records from CONN. 6 records from Herbarium specimens of Société des Sciences Naturelles et Mathématiques de Cherbourg (CHE). 1857 records from Plant specimens of Kushiro City Museum. 1 records from MfN - Fossil plants (Mesophytic). 45 records from The Fungal, Lichen and Plant Collections at the Herbarium Marburgense. 531 records from JODC Dataset. 38133 records from Pteridophyta collection of Museum of Natural and Environmental History, Shizuoka. 14824 records from Herbarium of Kitakyushu Museum of Natural History and Human History. 8 records from Staatliches Museum für Naturkunde Stuttgart, Herbarium. 1491 records from Paleobiology Database. 1182 records from Zooplankton communities in the coastal water of northeastern Hokkaido. 1 records from University of Alberta Vascular Plant Herbarium (ALTA-VP). 18 records from Masaryk University - Herbarium BRNU. 1 records from Colorado State University Herbarium. 1289 records from Plant specimens of the Museum of Yamagata University. 8 records from 16S rRNA Analysis of Osaka Bay Microbiomes. 77 records from Bell Museum plants. 2284 records from Seaweed (Plantae) Collection of the Seto Marine Biological Laboratory, Kyoto University. 52394 records from Angiospermatatophytina Collection of Saitama Museum of Natural History. 54008 records from Vascular plant specimens of Akita Prefectural Museum. 14 records from Nannofossil abundance of Hole 57-438. 1 records from Naturhistorisches Museum Mainz, Botanical Collection. 1250 records from Plant Observation Records of Japan. 17 records from A conspectus of the native and naturalized species of Nephrolepis (Nephrolepidaceae) in the world. 9 records from naturgucker. 15 records from Culture Collection of Microalgae and Zygnematophyceae Collection Hamburg (MZCH-SVCK). 6496 records from iNaturalist Research-grade Observations. 2 records from Taxonomic study of the genus Atkinsonia Stainton, 1859 (Lepidoptera, Stathmopodidae) in China, with descriptions of two new species. 17 records from Botany Division, Yale Peabody Museum. 2001 records from CSIC-Real Jardín Botánico-Colección de Musgos (MA-Musci). 9 records from ALCB - Herbário Alexandre Leal Costa. 24593 records from Spermatophyta specimens of Iwate Prefectural Museum. 6 records from CeDoc de Biodiversitat Vegetal: BCB-bryo. 17 records from SPF - Herbário da Universidade de São Paulo. 68 records from (Table T1) Neogene dynoflagellate cyst occurrence in ODP Hole 186-1151A sediments. 3359 records from Harvard University Herbaria: All Records. 383 records from HO AVH data. 52881 records from Vascular Plant Specimens of Kochi Prefectural Makino Botanical Garden. 1 records from HCF - Herbário da Universidade Tecnológica Federal do Paraná Campus Campo Mourão. 55 records from Continuous Plankton Recorder Dataset (SAHFOS). 1 records from PMSP herbarium - Prefeitura do Município de São Paulo - Herbário Virtual REFLORA. 2 records from New records of the larval forms Cerataspis monstrosa and Amphionides reynaudii (Crustacea: Decapoda) from the western tropical Atlantic. 64 records from Polish seed gene bank – historical passport data of accessions. 289 records from Bryophyte herbarium TRH, NTNU University Museum. 1 records from Propuesta para sistematizar la colección palinológica de polen reciente y fósil del IGLUNAM. 27 records from University of South Carolina, A. C. Moore Herbarium. 7 records from Family Geraniaceae in CSBG SB RAS herbarium collections (NS, NSK). 1 records from McGill University Herbarium Database. 25 records from Intermountain Herbarium (Utah State University). 3172 records from Algae specimens of Kanagawa Prefectural Museum of Natural History. 2 records from HUEFS - Herbario da Universidade Estadual de Feira de Santana. 1 records from Sistemática del género Polianthes L (Agavaceae). 8216 records from Bryophyte Collection of Natural History Museum and Institute, Chiba. 9 records from Paroxythrips gen. n. (Thysanoptera, Thripidae), associated with the gymnosperm order Araucariales in Japan and Australia. 1153 records from SP - Herbário do Estado "Maria Eneyda P. Kaufmann Fidalgo" - Coleção de Fanerógamas. 249 records from La colección briológica del Herbario Nacional (MEXU). Actualización 2000. 28 records from Microbial community in on-site tsunami sediment caused by the Great East Japan Earthquake. 21 records from BoGART - Berlin Botanical Garden (B) Accessions Database. 30004 records from Vascular Plant Specimens of Yamagata Prefectural Museum. 14 records from Rutgers University, Chrysler Herbarium - Bryophyte Collection. 3 records from Herbarium - Instituto Nacional de Pesquisas da Amazônia (INPA). 6 records from The Diatom Collection of Franz Josef Weinzierl at the Botanische Staatssammlung München. 19 records from Field Museum of Natural History (Botany) Seed Plant Collection. 14 records from Rutgers University, Chrysler Herbarium - Macroalgae Collection. 2777 records from Bryophyta Collection of Saitama Museum of Natural History. 57177 records from Gunma Museum of Natural History, Vascular Plant Specimen. 10000 records from Herbarium of Shinshu University. 1 records from Brown algae specimens of Komatsu City Museum. 5672 records from Ibaraki Nature Museum, Algae collection. 8 records from The fossil collection (F) of the Muséum national d'Histoire naturelle (MNHN - Paris). 123 records from Auckland Museum Botany Collection. 6 records from R-Tipos - Herbário do Museu Nacional - Tipos. 4 records from Family Primulaceae in Digital Herbaria of CSBG SB RAS (NS). 143 records from PRECIS. 266 records from Herbarium Senckenbergianum (FR). 35655 records from Plant Specimens of The Shimane Nature Museum of Mt. Sanbe. 834 records from MBM - Herbário do Museu Botânico Municipal. 3614 records from University of Tennessee Bryophyte Herbarium. 5 records from Bryophyte Collection of Museum of Natural and Environmental History, Shizuoka. 5 records from CeDoc de Biodiversitat Vegetal: BCN-Seeds. 10 records from CHSC - CSU Chico, Chico State Herbarium - Vascular Plants. 20 records from DDCA-metagenome. 115 records from SPF-Algae - Herbário da Universidade de São Paulo - Coleção de Algas. 29 records from University of California Museum of Paleontology. 5 records from PlantBank Records. 4444 records from Vascular plant specimens of Aomori City Forestry Museum. 2 records from Natural History Museum, University of Tartu. 1224 records from University of British Columbia Herbarium (UBC) - Vascular Plant Collection. 77 records from R - Herbário do Museu Nacional. 1 records from AIS Wildtype Populations of Arabidopsis. 9 records from University of Tennessee Vascular Herbarium. 26230 records from Vascular plants database of Atsugi City Museum. 15593 records from Bryophyte specimens of Nagano Environmental Conservation Research Institute, Nagano Prefecture. 210 records from SD Herbarium, San Diego Natural History Museum. 33 records from ESA - Herbário da Escola Superior de Agricultura Luiz de Queiroz. 1 records from Coastal Ecosystem Monitoring in the Tsugaru strait side of Shimokita. 1139 records from The Vascular Plant Collection at the Botanische Staatssammlung München. 1010 records from SP-Bryophyta - Maria Eneyda P. Kauffman Fidalgo. 6216 records from The System-wide Information Network for Genetic Resources (SINGER). 19 records from Herbarium specimens of Université de Montpellier 2, Institut de Botanique (MPU)). 7 records from Culture Collection of Algae. 9 records from University of Melbourne Herbarium. 1748 records from Mosses (S). 3 records from Western Australian Museum provider for OZCAM. 27 records from Fairchild Tropical Botanic Garden Virtual Herbarium Darwin Core format. 9044 records from Plant specimens of Obihiro Centennial City Museum. 4 records from A taxonomic synopsis of Altingiaceae with nine new combinations. 3 records from Australian National Wildlife Collection provider for OZCAM. 1460 records from Spermatophytes collection of Okinawa Prefectural Museum & Art Museum. 1253 records from Database of Native Plants in Taiwan. 30254 records from A global database for the distributions of crop wild relatives. 508 records from Polish gene bank – passport data of plants accessions which are important in human life. 1 records from Bothrocara nyx: a new species of eelpout (Perciformes: Zoarcidae) from the Bering Sea.. 2 records from BOTUw - Xiloteca "Profa. Dra. Maria Aparecida Mourão Brasil". 2 records from NatureShare. 684 records from Vascular Plant Herbarium, Oslo (O). 21794 records from Bryophyte specimens database of Mr. Tsutomu Kodama collection. 4 records from Kathryn Kalmbach Herbarium. 9 records from Type herbarium, Göttingen (GOET). 2 records from Marine Biological Sample Database, JAMSTEC. 139 records from North Carolina State University Vascular Plant Herbarium. 86 records from Estonian Museum of Natural History. 2 records from Olga Lakela Herbarium, University of Minnesota Duluth. 2 records from CMC Cincinnati Museum Center Invertebrate Paleontology. 2 records from Biologiezentrum Linz. 1898 records from Royal Botanic Gardens, Kew - Economic Botany Collection Specimens. 10 records from Range table from benthic foraminifers in ODP Hole 144-879A. 1 records from HUFU - Herbarium Uberlandense. 8 records from Biocultural Collection at the Natural History Museum of Denmark. 3 records from FUEL - Herbário da Universidade Estadual de Londrina. 17 records from The AAU Herbarium Database. 198 records from UTEP Plants (Arctos). 29750 records from Plant Specimen Database of Tama Forest Science Garden, Forestry and Forest Products Research Institute, Japan. 2 records from NU: KwaZulu-Natal Invasive Alien Species (1821-2011). 24 records from UF Florida Museum Paleobotany. 248 records from Metagenome analysis of picoeukaryotes from surface seawater. 1982 records from Plant specimens of Bihoro Museum. 21999 records from Vascular Plant Collection of Natural History Museum and Institute, Chiba. 1427 records from Taxon occurrence data for the FungalRoot database. 1 records from The Exsiccatal Series "Triebel, Microfungi exsiccati". 73 records from Nannofossil abundance of Hole 58-445. 4 records from Nannofossil abundance of Hole 58-443. 1 records from SJRP-Algae - Herbário de algas de São José do Rio Preto. 72349 records from Herbarium Specimens of Tokushima Prefectural Museum, Japan. 8 records from E. C. Smith Herbarium (ACAD). 6 records from Algaterra Types. 24 records from Rancho Santa Ana Botanic Garden Herbarium. 1 records from OBI - Robert F. Hoover Herbarium, Cal Poly State University. 633 records from Field Museum of Natural History (Botany) Bryophyte Collection. 80 records from Plant specimens of Mie Prefectural Museum. 11 records from INRA-Versailles Arabidopsis natural variants. 91954 records from Ibaraki Nature Museum, Vascular Plants collection. 4778 records from University of British Columbia Herbarium (UBC) - Bryophytes Collection. 2 records from Genus Allium in CSBG SB RAS herbarium collections (NS,NSK). 520 records from Royal Ontario Museum Green Plant Herbarium (TRT). 28294 records from NMNH Extant Specimen Records. 2586 records from Plant Specimens of Lake Biwa Museum. 457 records from Plant specimens of Kiritappu Wetland Center. 2940 records from Royal Botanic Gardens, Kew - Herbarium Specimens. 16 records from Duke University Herbarium Algae Collection. 28 records from UAM Herbarium (ALA), Algae Collection (Arctos). 16 records from Questagame weekly feed. 1 records from Ibaraki Nature Museum, Fungi collection. 100 records from Geneva Herbarium – De Candolle's Prodromus (G-DC). 188 records from Australian Antarctic Division Herbarium. 114584 records from Plant specimens depodited in Osaka Museum of Natural History, Japan. 814 records from RB - Rio de Janeiro Botanical Garden Herbarium Collection. 14392 records from Plant specimens of Horaiji-san Museum of Natural History Kichi T. collection. 1 records from Los musgos de México. 9104 records from Bryophyte specimens of Kanagawa Prefectural Museum of Natural History. 65 records from Foreign plant germplasm collections in Ghana. 4 records from Sediment bacterial 16S in Hachiro polder.. 1 records from Rutgers University, Chrysler Herbarium. 44 records from Genebank, National Institute of Agrobiological Sciences. 3 records from Vegetatively propagated Allium collection. 68746 records from The 6-7th National Survey on the Natural Environment: Vegetation Survey. 6 records from AWI-Herbarium Marine Macroalgae. 1411 records from Botany (UPS). 519 records from Herbarium Berolinense, Berlin (B). 88 records from The Bergius Herbarium. 2 records from Herbarium specimens of Herbiers Universitaires de Clermont-Ferrand (CLF). 12 records from UWBM Invertebrate Paleontology Collection. 5090 records from Spermatophyte collection of Himeji City Science Museum. 29 records from Fungus Collections at Staatliches Museum für Naturkunde Karlsruhe (Herbarium KR). 2319 records from Monitoring records of plant species in the Hakone region of Fuji-Hakone-Izu National Park, Japan, 2001-2010. 1 records from PACA-Bryophytes - Herbarium Anchieta - Aloysio Sehnem. 3 records from NMNH Paleobiology Specimen Records. 9964 records from Plant specimens of Tama City Cultural Foundation. 36 records from Some Angiosperm Data of the Forest Herbarium Ibadan (FHI) Nigeria. 360 records from Metagenomic community analysis of marine zooplankton using two plankton nets. 79 records from Colección de Solanales del Museo Botánico CORD - IMBIV. 21 records from University of Graz, Institute of Plant Sciences - Herbarium GZU. 2 records from MEXU/Colección Histórica. 17 records from Review of the mirine plant bug genus Eurystylus Stål from Japan and Taiwan (Hemiptera: Heteroptera: Miridae: Mirinae), with descriptions of two new species, a new synonymy and a new combination. 3010 records from Pteridophyta specimens of Iwate Prefectural Museum. 1 records from MPM Milwaukee Public Museum Herbarium. 2101 records from University of Michigan Herbarium. 2 records from University of Lethbridge Herbarium (LEA). 9 records from IAN herbarium - Embrapa Amazônia Oriental - Herbário Virtual REFLORA. 691 records from UCBG TAPIR Provider. 5 records from SDSU - San Diego State University Herbarium. 924 records from Diet analysis of Japanese sardine and Pacific round herring larvae. 13 records from Nannofossil abundance of Hole 31-296. 4 records from Hexacorallians of the world. 2 records from Vascular plant herbarium TRH, NTNU University Museum. 92659 records from Vascular plant specimens of Toyama Science Museum. 551 records from Comparative study in validity of three regions of 18S-rRNA for eukaryote amplicon sequence analyses. 8 records from Oskarshamn herbarium (OHN). 7 records from Flora of the Korean Peninsula Phase II. 14293 records from Spermatophyta collection of Museum of Natural and Environmental History, Shizuoka. 171 records from MGC Herbarium of University of Malaga (Spain): MGC-Algae dataset. 378320 records from Vascular plant specimens of National Museum of Nature and Science (TNS). 3 records from Dryinidae and Embolemidae (Hymenoptera, Chrysidoidea) from Anijima, Ogasawara Islands, Japan. 964 records from CSIC-Real Jardín Botánico-Colección de Hepáticas (MA-Hepat). 11 records from Plants of Scotia Sanctuary. 4906 records from Herbarium of Taiwan Forestry Research Institute. 3123 records from Plant specimens of Toyota City Nature Sanctuary (from non-museum circle). 3 records from Condon Fossil Collection. 201 records from R-Bryophyta - Herbário do Museu Nacional - Bryophyta. 4 records from Herbario de la Universidad de Sevilla, SEV-Historico. 736 records from Plant. 13 records from Grasses of the Forest Herbarium Ibadan (FHI) Nigeria. 378 records from The Erysiphales Collection at the University Halle-Wittenberg. 2 records from Herbario ABH (Universidad de Alicante). 13906 records from Long-term fauna and flora records of the experimental forests of the Forest Research Station of Hokkaido University, Japan. 6 records from Herbarium WRSL, Main Collection. 1 records from HUCS - Herbário da Universidade de Caxias do Sul. 1594 records from Plant Specimens of Wakayama Prefectural Museum of Natural History. 3396 records from The cryptogamy collection (PC) at the Herbarium of the Muséum national d'Histoire Naturelle (MNHN - Paris). 2 records from PACA-AGP - Herbarium Anchieta. 28 records from Natural History Museum Maastricht (NL) - Herbarium. 231 records from CAS Botany (BOT). 111 records from Herbario Nacional Colombiano (COL). 15 records from Moss herbarium, UiB. 31 records from Endemic Species Research Institute–Herbarium. 2 records from Base de datos para la xiloteca del Instituto de Biología de la UNAM. 16 records from UB - Herbário da Universidade de Brasília. 67329 records from Vascular plant specimens of Nagano Environmental Conservation Research Institute, Nagano Prefecture. 44739 records from Naturalis Biodiversity Center (NL) - Botany. 8841 records from Vascular Plants Collection of National Museum of Nature and Science. 1 records from The Fungal Collection of Helga Große-Brauckmann at the Botanische Staatssammlung München. 115 records from Computarización de la xiloteca Dr. Faustino Miranda del Instituto de Ecología, AC. 1 records from CSIC-Real Jardín Botánico-Colección de Hongos Histórica (MA-Funhist). 404 records from Microbial Culture Collection, National Institute for Environmental Studies. 5 records from Genus Medicago (Fabaceae) in CSBG Herbarium collections (NS, NSK). 4772 records from Pteridophyte specimens of Okinawa Prefectural Museum & Art Museum. 4 records from Anymals+plants - Citizen Science Data. 269448 records from Vascular Plant Specimen database of Kanagawa Prefectural Museum of Natural History. 4939 records from Tropicos Specimen Data. 8 records from Queensland Museum provider for OZCAM. 16 records from Desmidiaceae Engels. 70510 records from Bryophyte specimens of National Museum of Nature and Science (TNS). 8784 records from Bryophytes specimens of Akita Prefectural Museum. 81 records from Algae (S). 4714 records from International Barcode of Life project (iBOL). 4 records from Catálogo electrónico de especímenes depositados en el Herbario de la Universidad de Texas en Austin, Fase IV. 438 records from Occurrence data of woody plants in the Ginkakuzi-san National Forest. 14 records from Genus Rhododendron in Digital herbarium of CSBG SB RAS (NS, NSK). 832 records from Duke University Herbarium Bryophyte Collection. 44 records from Field Museum of Natural History (Botany) Pteridophyte Collection. 10 records from uncultured marine picoeukaryote strain:Peuk_V4_NWP2 Raw sequence reads. 223 records from Plant Specimens of The Cattle Museum. 3 records from Morphological and molecular diversity of rissoellids (Mollusca, Gastropoda, Heterobranchia) from the Northwest Pacific island of Hokkaido, Japan. 2 records from CABI Bioscience Fungus Collection. 1 records from Herbarium specimens of Jardins botaniques and Conservatoire Botanique of Nancy (NCY). 6 records from UPCB - Herbário do Departamento de Botânica. 73 records from Time course change of microbial community in tsunami sediment caused by the Great East Japan Earthquake. 1 records from Fungi specimen database of Kanagawa Prefectural Museum of Natural History. 3326 records from Plant specimens of Nasunogahara Museum. 3952 records from Vascular plant specimens of Shirakami Institute for Environmental Science, Hirosaki University. 2 records from Collections and observation data National Museum of Natural History Luxembourg. 5 records from Sedges of the Forest Herbarium Ibadan (FHI) Nigeria. 662 records from Natural History Museum, Vienna - Herbarium W. 9461 records from Fern (Pteridophyta) specimens of Toyama Science Museum. 543 records from UAM Herbarium (ALA), Cryptogam Collection (Arctos). 2069 records from Bryophyte herbarium, Göttingen (GOET). 34 records from University of Colorado, Museum of Natural History Herbarium Bryophyte Collection. 1 records from SPFw - Xiloteca do Instituto de Biociências da Universidade de São Paulo. 81 records from Diversity of bacterioneuston and bacterioplankton in coastal waters of Misaki, Japan. 95 records from Manchester Museum, University of Manchester, Botany Collection. 509 records from Gunma Museum of Natural History, Bryophyta Specimen. 1000 records from Plant specimens of Natural History Museum, Kishiwada City. 1 records from Botanical Research Intitute of Texas. 7811 records from EURISCO, The European Genetic Resources Search Catalogue. 1 records from Collections paléontologiques de l'Université Rennes 1. 3 records from Arizona State University Vascular Plant Herbarium. 2922 records from The New York Botanical Garden Herbarium (NY). 3073 records from Flora of Japan Specimen Database. 30 records from Naturalis Biodiversity Center (NL) - Paleobotany. 59 records from Institut Botanic de Barcelona (IBB-CSIC-ICUB), BC-Plantae. 62198 records from FKSE-Herbarium of Faculty of Symbiotic Systems Science, Fukushima University, Japan. 2 records from Gothenburg Herbarium - General (GBIF:IH:GB:Herbarium). 3 records from UCR - University of California, Riverside Herbarium - Vascular Plants. 931 records from Geneva Herbarium – General Collection (G). 2 records from Computarización de la base de datos del Banco Nacional de Germoplasma Vegetal - Fase 2. 302 records from CRIS data set. 10 records from Nordic Genetic Resources. 2110 records from Plant Specimens collections of the Kyushu University Museum. 7 records from Vascular Plant Collection - University of Washington Herbarium (WTU). 14 records from VIC - Herbário da Universidade Federal de Viçosa. 4 records from Diet analysis of Pacific Bluefin Tuna larvae. 5775 records from Royal Botanic Garden Edinburgh Herbarium (E). 297 records from CSIC-Real Jardín Botánico-Colección de Plantas Vasculares (MA). 4216 records from Plant specimens of Toyota City Nature Sanctuary. 1 records from herbario. 11 records from Royal BC Museum - Herbarium (V). 437 records from Gymnospermatatophytina Collection of Saitama Museum of Natural History. 5128 records from Ibaraki Nature Museum, Bryophyta collection. 174 records from IAC - Herbário do Instituto Agronômico de Campinas. 248 records from United Herbaria of the University and ETH Zurich. 1024 records from Lund Botanical Museum (LD). 4094 records from Natural History Museum (London) Collection Specimens. 35009 records from Vascular plants collection of Hiratsuka City Museum. 941 records from Plant specimens of Taga Town Museum, Shiga Pref., Japan. 47 records from UTEX Culture Collection of Algae at The University of Texas Living Algae Holdings. 9 records from CEPEC - Herbário do Centro de Pesquisas do Cacau. 55 records from The CPR Survey. 310 records from Botanic Garden of the Finnish Museum of Natural History. 11 records from University of New Hampshire - Macroalgal Collection. 1 records from Herbario Gaspar Xuarez (BAA) - Facultad de Agronomía - Universidad de Buenos Aires. 1 records from Herbarium of Namur. 71 records from SP-Algae - Herbário do Estado "Maria Eneyda P. Kaufmann Fidalgo - Coleção de Algas. 11 records from Actualización de las bases de datos de colecciones, especies en peligro de extinción, colecta y propagación de germoplasma. 3 records from The Fungal Collection at the Botanische Staatssammlung München. 1 records from HBGBryophyta - Herbarium Hamburgense. 4737 records from Phanerogamic Botanical Collections (S). 63 records from Capture of Primary Biodiversity Data for West African Plants. 111 records from NaGISA Project. 19175 records from Herbarium specimens of Hokkaido University Museum. 68 records from Medicinal plants and associated plant collections at Ghana Herbarium. 975 records from Bryophytes specimens of Okinawa Prefectural Museum & Art Museum. 9 records from MfN - Fossil plants (Cenophytic). 1 records from Desert Botanical Garden Herbarium. 3 records from Herbario Museo de La Salle Bogotá (BOG). 98 records from Jardin botanique de Montréal (JBM). 5288 records from Vascular plant specimens of Sugadaira Research Station, Mountain Science Center, University of Tsukuba. 4 records from SANT Herbarium vascular plants collection. 134 records from IPA - Herbário - IPA Dárdano de Andrade Lima. 5 records from Colección de Herbario. 3297 records from marine sediment metagenome Metagenome. 8 records from UFP - Herbário UFP - Geraldo Mariz. 18833 records from Herbarium Specimens of Bonin and Ryukyu Islands. 2182 records from University of British Columbia Herbarium (UBC) - Algae Collection. 14052 records from Plant specimens of Horaiji-san Museum of Natural History. 3 records from (Table T1) Calcareous nannofossil stratigraphy in ODP Hole 186-1150A sediments. 14692 records from The vascular plants collection (P) at the Herbarium of the Muséum national d'Histoire Naturelle (MNHN - Paris). 73 records from Algae herbarium TRH, NTNU University Museum. 175 records from ALA species sightings and OzAtlas. 12 records from (Table 2) Percent distribution of calcareous nannofossils at ODP Hole 125-782A. 3493 records from Plant specimens of Ishikawa Museum of Natural History. 2 records from T.B. Lee Herbarium Vascular Plant Collection. 2901 records from United States National Plant Germplasm System Collection. 162 records from Herbarium GAT. 2 records from CEN - Herbário da Embrapa Recursos Genéticos e Biotecnologia. 4 records from Gothenburg Herbarium - Types (GBIF:IH:GB:Herbarium). 1 records from Paleobotany Division, Yale Peabody Museum. 121709 records from Plant specimens in the Museum of Nature and Human Activities, Hyogo Prefecture, Japan. 55 records from Biological Resource Center, Department of Biotechnology, National Institute of Technology and Evaluation. 19 records from The Fungal Collection at the Senckenberg Museum für Naturkunde Görlitz. 3 records from Carnet en Ligne. 3 records from Flora of Sumatra: Vascular plant collection of selected families deposited at Herbarium of Andalas University (ANDA). 4 records from Michigan State University Herbarium Vascular Plants. 14256 records from Plant specimens of Tochigi Prefectural Museum. 3241 records from MEL AVH data. 1 records from UEC - Herbário da Universidade Estadual de Campinas. 60 records from Nagoya-Plants. 72 records from Allan Herbarium (CHR). 1 records from Bacteria Collection of the Seto Marine Biological Laboratory, Kyoto University. 4 records from ICN - Herbário do Instituto de Ciências Naturais. 2 records from Family Primulaceae in Digital Herbaria of CSBG SB RAS (NSK). 114 records from Bell Museum bryophytes. 2 records from Fossil occurrence of calcareous nannofossils from IODP Hole 319-C0009A. Data from some individual datasets included in this download may be licensed under less restrictive terms.
Keywords: GBIF; biodiversity; species occurrences